Role of herbicides and tillage on weeds and wheat (Triticum aestivum) yield in northern region of Madhya Pradesh - PARA, PAVAN KUMAR; KUSHWAH, SHAILENDRA SINGH; TIWARI, R K; SHARMA, KIRAN; SHARMA, B K (The Indian Journal of Agricultural Sciences, 2025)
The present study was carried out during winter (rabi) season of 2019–20 and 2020–21 at College of Agriculture, Rajmata Vijayaraje Scindia Krishi Vishwa Vidyalaya, Gwalior, Madhya Pradesh to study the role of herbicides and tillage on weeds and wheat (Triticum aestivum L.) yield in the northern region of Madhya Pradesh. The experiment was laid out in a split-plot design (SPD) with three replications. The treatments comprise 21 combinations with tillage systems, namely conventional tillage (CT), minimal tillage (MT) and zero tillage (ZT), as main plots and seven weed control practices, viz. sulfosulfuron (30 g/ha); metsulfuron-methyl (4 g/ha); clodinafop (60 g/ha); sulfosulfuron + metsulfuron-methyl (30 + 2 g/ha); clodinafop + metsulfuron-methyl (60 + 4 g/ha), two hand weeding at 30 and 60 days after sowing (DAS), as a sub plot. Both biomass and weed density were reduced by 45% in ZT and 19% in MT and grain yield was increased by 20% in ZT and 14% in MT compared to CT at 60 days after sowing. Two-hand weeding with ZT produced the maximum grain production (5.2 t/ha), which was statistically comparable to applying clodinafop + metsulfuron (60 + 4) g/ha under the ZT. ZT practice coupled with two-hand weeding (30 and 60 DAS) provided 43.7% higher gross profit than CT with two-hand weeding (30 and 60 DAS); however, net profit increased by 18%, B:C (3.11) under ZT with clodinafop + metsulfuron (60 + 4) g/ha than CT with clodinafop + metsulfuron- methyl. Because of the increased production costs, the B:C was lower in all herbicidal treatments using CT and MT. Consequently, ZT in conjunction with clodinafop + metsulfuron (60 + 4 g/ha) in wheat can be suggested for effective control of weeds, enhanced yield and profitable production.